The Transition From Latent to Active Labor and Adverse Obstetrical Outcomes. Issue 4 (April 2020) - Rosenbloom, Joshua I.; Woolfolk, Candice L.; Wan, Leping; Stout, Molly J.; Tuuli, Methodius G.; Macones, George A.; Cahill, Alison G.
Abstract : (Abstracted from Am J Obstet Gynecol 2019;221:487.e1–487.e8) Previously defined time limits for latent labor (defined as ending at 6 cm) have been removed by recommendations on preventing primary cesarean delivery (which also urge clinicians to avoid cesarean delivery for labor abnormalities in the latent phase). However, relatively little is known about the implications of labor curve abnormalities from 4 to 6 cm and subsequent outcomes.